Evaluation of admissions and inappropriate referrals to pediatric gastroenterology, hepatology and nutrition outpatient clinics - Şeker, Gül; Orhan, Özhan (The European Research Journal, 2025)
Objective: The aim of this study was to examine the diagnostic profiles of patients admitted to pediatric gastroenterology, hepatology, and nutrition outpatient clinics within the scope of the state service obligation and to determine the reasons for inappropriate referrals. Methods: A total of 10,235 patients admitted to the pediatric gastroenterology, hepatology and nutrition outpatient clinics of Mardin Training and Research Hospital between 2022 and 2023 were retrospectively analyzed. Data were analyzed using SPSS 21.0 software according to demographic and clinical variables such as age, gender, reasons for admission and diagnoses. Results: Of the patients examined, 49.1% were girls and 50.9% were boys, and the most common reason for presentation was inadequate weight gain with a rate of 46%. However, malnutrition or another nutritional disorder was not detected in 28% of the patients referred with a diagnosis of inadequate weight gain. Malnutrition was diagnosed in a total of 1,710 cases, of which 8.2% were mild malnutrition, 5.3% were moderate malnutrition, and 4.2% were severe malnutrition. No pathological findings were found in 40.8% of the applicants. It was also found that most of the complaints of constipation and diarrhea, which are common reasons for admission, can be effectively treated in primary and secondary health care services. Conclusions: The results of the study show that a significant proportion of referrals to pediatric gastroenterology outpatient clinics are unnecessary and that referrals can be reduced by evaluating these patients in primary and secondary care, thereby increasing the efficiency of health care services.